PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) AKIBAT PEMBERIAN KOMPOS AMPAS KELAPA DI MEDIA PODSOLIK MERAH KUNING - Kurniawan, Tardi; Rosmalinda, Rosmalinda; Kristina Maharani, Vika (Politeknik Negeri Ketapang, 2024)
Cocoa is a type of tree that originates from South America and is now widely cultivated in other countries, including Indonesia. In certain areas in Indonesia, quality land has begun to decrease. An alternative that can be utilized is the use of Red Yellow Podsolic (PMK) soil to plant cocoa. One effort to increase soil productivity and increase the organic matter content in PMK soil is by adding coconut pulp compost as an alternative to inorganic fertilizers. This study aims to determine the effect of giving coconut pulp compost on the growth of cocoa seedlings and what is the best dose of coconut pulp compost that affects the growth of cocoa seedlings in PMK media. This study used a non-factorial Completely Randomized Design (CRD) with 5 treatments and 5 replications. Each treatment consisted of 3 samples so that 75 plant samples were obtained. The treatments were: B0: without coconut pulp compost (0 g/polybag), B1: coconut pulp compost dose of 200 g/polybag, B2: coconut pulp compost 250 g/polybag, B3: coconut pulp compost 300 g/polybag, B4: coconut pulp compost 350 g/polybag. The data obtained were analyzed using Analysis of Variance (ANOVA) and further tested by Duncan's Multiple Range Test (DMRT) at the 5% level. Based on the analysis of variance, the provision of coconut pulp compost had a significant effect on seedling height (20.60 cm), dry weight of the shoot (1.61 g), and dry weight of the roots (0.41 g) which could increase the growth of cocoa seedlings. The best treatment was the provision of coconut pulp compost dose of 350 (g/polybag).